Enhancing Customer Satisfaction in Automotive Service Centers: A Quantitative Analysis: Meningkatkan Kepuasan Pelanggan di Pusat Layanan Otomotif: Analisis Kuantitatif" (In Bahasa Indonesia) - Katerina Putri Prameswari; Hasan Ubaidillah (Academia Open, 2024)
This quantitative research study aims to elucidate the impact of individual skills, facilities, and customer relationship management on customer satisfaction within the context of automotive service centers. The study, conducted with a sample of 100 Honda customers, employed cluster random sampling and Likert scale surveys. The findings reveal that individual skills significantly and positively influence customer satisfaction (p < 0.05, t = 7.119), as do facility-related factors (p < 0.05, t = 3.204). However, customer relationship management, when considered individually, does not exhibit a significant impact (p > 0.05, t = 0.311). Notably, when analyzed collectively, these variables demonstrate a substantial and positive effect on customer satisfaction (p < 0.05). These results underscore the importance of individual skills and service facilities in bolstering customer satisfaction in the automotive service industry, while suggesting potential areas for improvement in customer relationship management practices. This research holds implications for service providers seeking to enhance customer satisfaction and loyalty. Highlight: Individual skills and service facilities have a significant positive impact on customer satisfaction in automotive service centers. Customer relationship management, while not individually significant, contributes positively when considered collectively with other factors. This research offers valuable insights for service providers looking to improve customer satisfaction and loyalty in the automotive service industry. Keywords: Automotive Service Centers, Customer Satisfaction, Individual Skills, Facilities, Customer Relationship Management